The work of the pedagogical coordinator during the Covid-19 pandemic (Olhar de Professor, 2024)
The objective of this work was to elaborate a systematic review on academic production regarding the work of the pedagogical coordinator during the period of the Covid-19 pandemic, with the purpose of emphasizing its challenges and actions taken throughout this period of time. To select the academic work, four comprehensive data bases were accessed: Portal de Periódicos da Capes (Coordenadoria de Aperfeiçoamento de Pessoal de Nível Superior/ Higher Education Personnel Improvement Coordination), Scientific Electronic Library Online (SciELO), Biblioteca Digital de Teses e Dissertações (BDTD – Digital Library of Theses and Dissertations) and Google Scholar. Supported by references such as Placco, Souza and Almeida (2012), Miziara, Ribeiro e Bezerra (2014) and Cunha and Ometto (2013), the eighteen essays were divided into four categories for further analysis. The results point to the broadening of the coordinator’s responsibilities during the period but also reaffirm this position as essential to the school’s progress, whether it is remote or face-to-face.
Keywords: Pedagogical coordinator.; Pandemic.; Remote classes.